القياس و الإفصاح المحاسبي على تكاليف المسؤولية الاجتماعية دراسة ميدانية لعينة من المؤسسات الاقتصادية – سوق أهراس - ياسمين حمادنة; ضحى اولادزاوي (My University, 2021)
The aim of this research is to study measurement and accounting disclosure on the costs of social responsibility, and the importance of the research comes from the urgent need for economic units to recognize their social responsibility and adhere to disclosing that in detail, and from finding methods for measurement and accounting disclosure about the various social activities that these institutions carry out towards Various stakeholders from employees, environment, society, customers and product development. The research concluded that institutions in today's world must delve into their depths and seek creativity in adopting them through the accounting measurement of their social responsibility and their disclosure separately and comprehensively. Among the most prominent recommendations of the study is that the state motivate economic companies that disclose the costs of social responsibility, such as exempting them from taxes or other facilities in return for their social contribution. .......................................................... هدفت الدراسة إلى تبيان القياس والإفصاح المحاسبي على تكاليف المسؤولية الاجتماعية، وتأتي أهمية البحث من الحاجة الماسة إلى ضرورة اعتراف الوحدات الاقتصا دي ة بمسؤوليتها الاجتماعية وتقيدها بالإفصاح عن ذلك بشكل مفصل، ومن ثم إيجاد أساليب للقياس والإفصاح المحاسبي عن مختلف الْنشطة الاجتماعية التي تقوم بها هذه المؤسسات تجاه مختلف الْطراف ذات المصالح من العاملي، البيئة ، المجتمع ، العملاء وتطوير المنتج . وقد خلص البحث إلى أن المؤسسات في عالم اليوم يجب عليها أن تغوص في أعماقها، وأن تسعى نحو الإبداع في تبنيها من خلال القياس المحاسبي لمسؤوليتها الاجتماعية والإفصاح عنها بشكل منفصل وشامل . ومن أبرز توصيات الدراسية أن تقوم الدولة بتحفيز الشركات الاقتصادية التي تفصح عن تكاليف المسؤولية الاجتماعية مثل إعفائها من الضرائب أو غيرها من التسهيلات مقابل مساهمتها الاجتماعية